Disfungsi ereksi pada penyakit kardiovaskular - Sasube, Nancy; Rampengan, Starry H. (Jurnal Biomedik : JBM, 2016)
Abstract: Erectile dysfunction (ED) is common among cardiovascular disease (CVD) patients. It is an important component of the quality of life. Moreover, it also confers an independent risk for future CV events. There is usual a 3-year time frame between the onset of ED symptoms and a CV event which offers an opportunity for risk mitigation. Thus, sexual function should be incorporated into CVD risk assessment for all males. Algorithms for the management of patient with ED have been proposed according to the risk for sexual activity and future (comprising of both lifestyle changes and pharmacological treatment) improve overall vascular health, including sexual function. Proper sexual counselling improves the quality of life and increase adherence to medication. Testosterone assessment may be useful for both diagnosis of ED, risk stratification, and further management. There are issues to be addressed, such as whether PDE5 inhibitors reduce CV risk. Management of ED requires a collaborative approach and the role of the cardiologist is pivotal.Keywords: cardiovascular disease, erectile dysfunction, sexual functionAbstrak: Disfungsi ereksi (DE) umumnya ditemukan pada pasien dengan penyakit kardiovaskular. DE merupakan komponen penting terhadap penurunan kualitas hidup pada laki-laki dan merupakan indikator terhadap risiko kejadian penyakit kardiovaskular di masa depan. Terdapat jangka waktu sekitar 3 tahun antara munculnya DE dan kejadian penyakit kardiovaskular, sehingga masih ada kesempatan untuk mencegah risiko yang akan terjadi. Dengan demikian fungsi seksual harus dimasukkan dalam penilaian risiko penyakit kardiovaskular pada semua laki-laki. Algoritma untuk penanganan pasien DE telah dirumuskan sesuai dengan risiko aktivitas seksual dan kejadian penyakit kardiovaskular di masa depan. Beberapa pendekatan untuk mengurangi resiko penyakit kardiovaskular terdiri dari perubahan gaya hidup dan pengobatan farmakologi dapat meningkatkan kesehatan termasuk fungsi seksual. Konseling seksual yang tepat dapat meningkatkan kualitas hidup dan meningkatkan kepatuhan terhadap pengobatan. Penggunaan testosteron dan inhibitor PDE5 dapat bermanfaat dalam pengobatan DE. Penanganan DE memerlukan kerjasama dari berbagai bidang spesialistik termasuk peran dari kardiologis.Kata kunci: disfungsi ereksi, fungsi seksual, penyakit kardiovaskular